Metatarsal Transfer for Atypical Phenotype of Foot Polydactyly: A Case Report - Yasufumi Makiuchi; Izumi Ban; Yuji Kuroyanagi; Kiyonori Harii (Journal of Plastic and Reconstructive Surgery)
Polydactyly of the foot is one of the most frequently observed congenital deformities. Although resection of the extra phalanx generally leads to a favorable outcome, functional disorder may sometimes occur. We present a rare case of bilateral metatarsal-type polydactyly of the foot. The patient underwent resection of the bilateral extra phalanxes at the age of 1, followed by reoperation at the age of 9 years due to the complaint of pain on the lateral side of his left anterior foot while walking. Therefore, we performed metatarsal transfer to preserve the articulation between the extra metatarsal bone and fifth phalanx, which led to a favorable outcome. In complicated cases, we believe that a “wait and see” strategy is reasonable to facilitate appropriate preoperative evaluation, taking into account the future growth of the reconstructed toes and preserving the foot function.